The Effect of Rosella (Hibiscus sabdariffa Linn) on Insulin Resistance in Patients with Type 2 Diabetes Mellitus: A Randomized Clinical Trial - Sarbini, Dwi; Huriyati, Emy; Sadewa, Hamim; Wahyuningsih, Mae Sri Hartati (Universitas Muhammadiyah Surakarta, 2019)
Insulin resistance in Type 2 Diabetes Mellitus (T2DM) is indicated with high fasting blood glucose level, fasting insulin and HOMA-IR. The long-time consume of diabetes drugs would bring harm. Rosella can be used as a complementary drug to improve insulin resistance and prevent T2DM complications. This study seeks the effect of consuming Rosella on fasting blood glucose, fasting insulin and HOMAIR in T2DM patients.The study design used double-blinded & placebo-controlled randomized clinical trial with intervention (placebo and Rosella) for 8 weeks. The sample consisted of 52 T2DM outpatients at Health Office Yogyakarta City. Measurement of fasting blood glucose was conducted through GOD-PAP method, fasting insulin was measured by MEIA, HOMA-IR was calculated with HOMA Calculator 2.2.3 Version. Analysis of the influence of Rosella on fasting blood glucose, fasting insulin and HOMA-IR level in one group were tested with the Wilcoxon Signed Test and the effect between groups were tested through Mann Whitney with a significance level of 95%.Rosella consumption can reduce fasting blood glucose, fasting insulin and HOMA-IR levels. There was a significant effect of Rosella administration on decreasing fasting blood glucose level in T2DM patients (p=0.001) but there were no significant effect on decreasing fasting plasma insulin level and HOMA-IR levels (p=0.932 and p=0.368). Rosella can improve insulin resistance by reducing fasting blood glucose levels, fasting insulin levels and HOMA-IR values.